A Novel Brushless Wound Rotor Synchronous Machine Utilizing Inherent Sub-Harmonic Component - Muhammad Ahsan Ul Haq; Haroon Farooq; Asif Hussain; Syed Abdul Rahman Kashif (IEEE Access)
Permanent magnet synchronous machines (PMSMs) contain a simple structure, high efficiency, and simple control. However, their cost has increased significantly due to the increase in the price of permanent magnets. Wound rotor synchronous machines (WRSMs) can be used as an alternative to PMSMs. In WRSMs, there is no need for permanent magnets as the rotors of these machines are electromagnets. However, there is the sparking issue which consequently requires regular maintenance of slip rings and carbon brushes. The research focus in recent times is to eliminate the brushes and slip rings in the conventional WRSMs. This manuscript presents a novel brushless wound rotor synchronous machine (BL-WRSM) utilizing an inherent subharmonic component (SHC). The proposed design achieves a brushless function by utilizing the inherent SHC of the stator magnetomotive force (MMF) inherently available in the air gap. As compared to the existing distributed winding BL-WRSM, the proposed BL-WRSM does not involve any extra circuitry at the stator side, additional inverter, or special stator winding arrangements. Utilizing SHC provides benefits such as reduced torque ripple and symmetrical flux distribution as compared to existing brushless machines. There are two distinct windings present on the rotor in the suggested BL-WRSM. These are field winding (FW) and harmonic winding (HW). A rectifier connects these windings in parallel with one another. The SHC of stator MMF generates an AC voltage in HW. This AC voltage is converted to DC by a rectifier, which powers the rotor FW. Validation of brushless operation of the suggested 8-pole, 12-slot machine is conducted through a 2-dimensional finite element analysis with the help of JMAG software. The suggested topology results in desired torque at rated speed with low torque ripples.